Reduced overhead for intra–cluster and inter–cluster sensor–to–actor communications in IEEE 802.15.4 networks. (2nd January 2014) - Cuevas, Ángel; Urueña, Manuel; Cuevas, Rubén; Crespi, Noël
This paper proposes a novel way to enable sensor–to–actor communications in wireless sensor and actor networks (WSANs) that only requires a simple modification to the IEEE 802.15.4 header. Although this standard includes the definition of sensor–to–actor communication, it does not address how to provide it. Our proposal is able to provide this sensor–to–actor communication at the 802.15.4 MAC layer, thereby reducing the overhead of the additional network header, and achieving an important reduction of the energy consumption. In addition, avoiding the need of a network layer with full routing capabilities in the sensors provides further memory, processing and communications saving. Moreover, this paper considers two scenarios for sensor–to–actor communications: intra–cluster and inter–cluster. The former enables the communication among sensors/actors at the same wireless sensor and actor network, and the latter allows sensors/actors located in geographically separated cluster to communicate transparently as if they were in the same WSAN.